2006
DOI: 10.2118/99329-pa
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Initial Water Saturation on Recovery by Spontaneous Imbibition in Gas/Water/Rock Systems and the Calculation of Relative Permeability

Abstract: It has been a challenge to understand why recovery by spontaneous imbibition could both increase and decrease with initial water saturation. To this end, mathematical models were developed with porosity, permeability, viscosity, relative permeability, capillary pressure, and initial water saturation included. These equations foresee that recovery and imbibition rate can increase, remain unchanged, or decrease with an increase in initial water saturation, depending on rock properties, the quantity of residual g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 10 publications
4
23
0
Order By: Relevance
“…It is found from Table 2 that values of the time exponent lie in the range of 0.07-0.50. The porosities of experimental Table 3 Comparisons on the experimental and analytical results for time exponent from building material samples (Karoglou et al 2005 Table 4 Comparisons on the experimental and analytical results for time exponent from chalk (Li and Horne 2004), Berea (Li et al 2006), and Bentonite clay (Brú and Pastor 2006 samples such as paper, fabrics, and paper were not provided in their tests. So, the comparison between the model predictions and experimental results is not provided in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is found from Table 2 that values of the time exponent lie in the range of 0.07-0.50. The porosities of experimental Table 3 Comparisons on the experimental and analytical results for time exponent from building material samples (Karoglou et al 2005 Table 4 Comparisons on the experimental and analytical results for time exponent from chalk (Li and Horne 2004), Berea (Li et al 2006), and Bentonite clay (Brú and Pastor 2006 samples such as paper, fabrics, and paper were not provided in their tests. So, the comparison between the model predictions and experimental results is not provided in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Karoglou et al presented a simple first-order kinetic model, which can be used to predict the capillary rise height as a function of average pore radius. The present model predictions are also compared to the experimental data from chalk (Li and Horne 2004), Berea (Li et al 2006), and Bentonite clay (Brú and Pastor 2006) as shown in Table 4. From Tables 3 and 4 it is found that the present model predictions of the time exponent k increase with porosity increasing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many papers have been published to characterize and scale spontaneous water imbibition in both oil/water/rock systems Tong et al 2001;Zhou et al 2001;Babadagli 2001;Kashchiev and Firoozabadi 2002;Civan and Rasmussen 2001;Akin et al 2000;Cil et al 1998;Perkins and Collins 1960;Mattax and Kyte 1962;Du Prey 1978;Hamon and Vidal 1986;Reis and Cil 1993;Cuiec et al 1994;Ma et al 1995;Chen et al 1995;Zhang et al 1996;Al-Lawati and Saleh 1996;Babadagli 1997;Li and Horne 2002) and gas/liquid/rock systems Horne 2001, 2004a;Li et al 2006;Handy 1960). However, few have included the effects of capillary pressure, relative permeability (both wetting and nonwetting phases), wettability, and gravity simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…The porous-medium approach was used to calculate two-phase relative permeabilities. Li et al (2006) and Li and Horne (2008) proposed a numerical-simulation approach without direct specification of relative permeability functions. Using this approach, it was not necessary to impose relative permeability functions as input to the simulator to conduct the numerical simulations of two-phase fluid flow.…”
Section: Introductionmentioning
confidence: 99%